2012
DOI: 10.1021/es301969m
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Retention of Colloids at Rough Rock Surfaces

Abstract: The spatial deposition of polystyrene latex colloids (d = 1 μm) at rough mineral and rock surfaces was investigated quantitatively as a function of Eu(III) concentration. Granodiorite samples from Grimsel test site (GTS), Switzerland, were used as collector surfaces for sorption experiments. At a scan area of 300 × 300 μm(2), the surface roughness (rms roughness, Rq) range was 100-2000 nm, including roughness contribution from asperities of several tens of nanometers in height to the sample topography. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…It therefore appears plausible that Na humate attaches onto the rougher surfaces of unwashed Dorsilit8 sand, but not onto the smoother acid-washed surfaces of glass beads and Ottawa sand. The total interaction energy as sum of the van der Waals and electrical double layer forces between colloids and glass bead collectors 34 and rough rock surfaces 35 has previously been shown to decrease with increasing collector roughness, with colloids being attached preferentially by sorption onto surfaces with a high density of small protuberances. Similarly, the attachment of Na humate to the surfaces of relatively smooth glass beads and Ottawa sand was also expected to be less than to the rougher surfaces of unwashed Dorsilit8 sand.…”
Section: Resultsmentioning
confidence: 99%
“…It therefore appears plausible that Na humate attaches onto the rougher surfaces of unwashed Dorsilit8 sand, but not onto the smoother acid-washed surfaces of glass beads and Ottawa sand. The total interaction energy as sum of the van der Waals and electrical double layer forces between colloids and glass bead collectors 34 and rough rock surfaces 35 has previously been shown to decrease with increasing collector roughness, with colloids being attached preferentially by sorption onto surfaces with a high density of small protuberances. Similarly, the attachment of Na humate to the surfaces of relatively smooth glass beads and Ottawa sand was also expected to be less than to the rougher surfaces of unwashed Dorsilit8 sand.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed surface roughness only qualitatively, but other authors also used quantitative approaches, e.g. vertical scanning interferometry (Darbha et al, 2010(Darbha et al, , 2012 to determine the surface roughness.…”
Section: Colloid Deposition Attributesmentioning
confidence: 99%
“…Fischer and colleagues [28] relayed that geochemistry affects surface roughness, with the elements U, P, Cu, and Zn on black slates being inversely correlated with (the surface parameter) F. More recently, Fischer and colleagues [29] discovered a positive linear correlation between surface roughness, on surfaces of <100 nm, and adsorbed particle density. They also found a minimum roughness range (of at least 50 nm for particles with diameter of 1 µm) for initial colloid deposition, which occurred primarily at micrite (mainly calcite, but also with traces of quartz and ankerite) grain boundaries, where surface steps were established, forming small protrusions [30]. A scan area of 300 × 300 µm revealed that increased roughness increases the deposition of colloids, but chiefly at low concentrations.…”
Section: Discussionmentioning
confidence: 95%